The Effect of Azolla microphylla Compost and Biocon-NP Biofertilizer on Soybean (Glycine max (L.) Merril) Growth in Lapindo Mud Planting Media - Lena, Fallery Elisia Malva; Rahayu, Yuni Sri; Rahajeng, Saptini Mukti (LenteraBio : Berkala Ilmiah Biologi, 2025)
This research describes the effect of Azolla microphylla compost and Biocon-NP biofertilizer on the growth of soybean plants (Glycine max (L.) Merrill) on lapindo mud planting media. This study used an experimental method with a Randomised Group Design involving two factors, Azolla microphylla compost with concentrations of 0 grams, 100 grams, 200 grams, and 300 grams and Biocon-NP biofertilizer concentrations of 0 ml, 125 ml, and 150 ml with three replications using vegetative phase observation parameters including plant height, number of leaves, plant wet biomass, root length, and active root nodule biomass. Generative phase parameters included flowering time, number of pods, and pod biomass. Data analysis used Two-Way Analysis of Variance followed by Duncan’s test (p < 0.05). The results showed that the treatment of Azolla microphylla compost 200 grams + Biocon-NP biofertilizer 150 ml gave a significant effect with the highest results in the parameters of the number of leaves, plant wet biomass, root length, wet biomass of active root nodules, number of pods, and pod biomass. This study also showed that applying Azolla microphylla compost and Biocon-NP biofertilizer accelerated growth to the generative phase.